POLICY, SCIENCE AND SOCIETY INTERACTION†. (18th March 2014) - Tollefson, L.; El Atfy, H.; Facon, T.; Kerc, A.; Tyagi, Avinash C.; Gundogdu, Huseyin; Schultz, Bart
ABSTRACT Irrigated agriculture is undergoing rapid change and is facing issues related to climate change, population growth, consumption patterns, competition for resources and cost of development. The challenge is whether water availability for irrigation along with rainfed production will be sufficient to meet growing food demand and improve global food security. Traditionally governments have been responsible for developments in the irrigation sector through planning, design and construction of projects. Trends toward decentralization, fiscal crisis and growth of the private sector have led government to divest some of its role to user organizations and the private sector. This has been known as the participatory approach to irrigation management and has been adopted widely by many countries with a range of institutional arrangements. Many irrigation and drainage schemes worldwide perform below their capacity. To modernize and improve this capacity will require innovation and technical advancement, but in addition issues of policy, governance, management and institution must be addressed. Copyright © 2014 John Wiley & Sons, Ltd.